A Synthetic Erectile Optogenetic Stimulator Enabling Blue‐Light‐Inducible Penile Erection1. Issue 20 (18th March 2015) - Kim, Taeuk; Folcher, Marc; Baba, Marie Doaud‐El; Fussenegger, Martin
Abstract Precise spatiotemporal control of physiological processes by optogenetic devices inspired by synthetic biology may provide novel treatment opportunities for gene‐ and cell‐based therapies. An erectile optogenetic stimulator (EROS), a synthetic designer guanylate cyclase producing a blue‐light‐inducible surge of the second messenger cyclic guanosine monophosphate (cGMP) in mammalian cells, enabled blue‐light‐dependent penile erection associated with occasional ejaculation after illumination of EROS‐transfected corpus cavernosum in male rats. Photostimulated short‐circuiting of complex psychological, neural, vascular, and endocrine factors to stimulate penile erection in the absence of sexual arousal may foster novel advances in the treatment of erectile dysfunction.